Legislative Shifts and Tax Compliance: The Impact of Receipt Issuance Requirements on Fiscal Verification in Slovenia - Bobek, Vito; Zver, Monika; Horvat, Tatjana (Naše gospodarstvo/Our economy, 2026)
This article investigates the behavioural impact of a 2022 legislative change in Slovenia that temporarily suspended the mandatory issuance of customer receipts while retaining the obligation to verify transactions with the tax authority (FURS) fiscally. Based on administrative data at the level of six economic sectors for 2019-2023, the study utilises t-tests and correlations to analyse the changes in the number of verified receipts during and after the legal change. Results show a significant reduction in the volume of receipts in some cash-based sectors, such as hospitality and retail, for which there is evidence of a decline in the perceived level of enforcement visibility based on our payment data. The impact was reversed in the year 2023 after the reimplementation of the policy. This study contributes to the tax morale and fiscal enforcement literature by demonstrating that even minimal procedural changes can yield substantial behavioural responses. Its implications are relevant for tax administrations seeking to balance simplification with deterrence.